2013
DOI: 10.1088/0004-637x/763/2/129
|View full text |Cite
|
Sign up to set email alerts
|

KECK SPECTROSCOPY OF 3 <z< 7 FAINT LYMAN BREAK GALAXIES: THE IMPORTANCE OF NEBULAR EMISSION IN UNDERSTANDING THE SPECIFIC STAR FORMATION RATE AND STELLAR MASS DENSITY

Abstract: The physical properties inferred from the spectral energy distributions (SEDs) of z > 3 galaxies have been influential in shaping our understanding of early galaxy formation and the role galaxies may play in cosmic reionization. Of particular importance is the stellar mass density at early times, which represents the integral of earlier star formation. An important puzzle arising from the measurements so far reported is that the specific star formation rates (sSFRs) evolve far less rapidly than expected in mos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

110
625
8

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(743 citation statements)
references
References 99 publications
(218 reference statements)
110
625
8
Order By: Relevance
“…We find good agreement with observations (Pérez- González et al 2008;Stark et al 2013;Tomczak et al 2014;Grazian et al 2015;Song et al 2015) taking into account the scatter in observations at z < 2, and the uncertain but potentially significant contribution of massive quiescent galaxies at low redshift. (2015); Song et al (2015).…”
Section: Stellar Masses and Agessupporting
confidence: 90%
“…We find good agreement with observations (Pérez- González et al 2008;Stark et al 2013;Tomczak et al 2014;Grazian et al 2015;Song et al 2015) taking into account the scatter in observations at z < 2, and the uncertain but potentially significant contribution of massive quiescent galaxies at low redshift. (2015); Song et al (2015).…”
Section: Stellar Masses and Agessupporting
confidence: 90%
“…This is determined by observed rest-frame ultraviolet luminosity functions (e.g. Bouwens et al, 2006;Reddy et al, 2008;Oesch et al, 2010) at high redshift and the observed main sequence (Noeske et al, 2007b;Stark et al, 2013).…”
Section: Relationship To Normal Galaxies: the Infrared Main Sequencementioning
confidence: 98%
“…This however assumes that high-J CO transitions trace the same region as low-J CO lines, however this often cannot be the case as the integrated SMG star formation history would exceed the local baryon density . Similarly, potential discrepancies in the integrated cosmic star formation history, and evolution of the stellar mass function may imply either a bottom light or top heavy IMF at high-z, with the idea that such an IMF would cause inferred SFRs to decrease, and bring the two values into agreement (Hopkins & Beacom, 2006;Elsner et al, 2008;Pérez-González et al, 2008;Wilkins et al, 2008), though issues related to luminosity function integration as well as nebular line contamination in stellar mass estimates may relieve some of these tensions (Reddy & Steidel, 2009;Stark et al, 2013). van Dokkum (2008 suggested that the color evolution of early type galaxies at z ∼ 1, combined with their mass to light ratios may be well described by a bottom light IMF, though note in van Dokkum & Conroy (2012) that the same observations could be consistent with a Salpeter IMF.…”
Section: Stellar Imfmentioning
confidence: 99%
“…At very high redshift (z ∼ 7 and above) the inclusion of nebular emission in SED templates can affect stellar mass estimates by up to 0.4 dex where strong lines intersect the relevant broad-band filters (e.g. Schaerer & de Barros 2009;Stark et al 2013;Wilkins et al 2013b). The choice of SPS model has also been demonstrated to affect physical properties inferred from observations and photometric properties predicted by galaxy formation simulations (e.g.…”
Section: Introductionmentioning
confidence: 99%